PENGARUH PROMOSI, KUALITAS LAYANAN, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN TIKET BIOSKOP CGV DI DKI JAKARTA - Niken Diah Fitriana; Nobelson Nobelson; Iwan Kresna Setiadi; Yudi Nur Supriadi (Gapenas Publisher, 2023)
Cinema is a place that is used as a means of entertainment for some individuals after facing the busy daily activities that are carried out. They think that watching movies in cinemas can relieve stress, is a place for relaxation, and can also be enjoyed by all ages which makes it a suitable place for family entertainment. Currently, there are several phenomena that influence the decision to purchase CGV cinema tickets so the formulation of the problem is obtained regarding whether promotion, service quality, and price can influence purchasing decisions. This research was conducted with the aim of proving whether promotion, service quality, and price influence purchasing decisions. The target population in this study were all consumers from CGV cinemas in DKI Jakarta with a sample of 100 respondents using a non- probability sampling technique and a purposive sampling method. This research uses quantitative methods. The tool used is Partial Least Square (PLS) with Smart PLS 3.0 software. The results of this study indicate that the promotion, service quality, and price variables have a significant positive influence on the decision to purchase CGV cinema tickets in DKI Jakarta. Based on the t-statistic test, the variables studied have the same effect, but the promotion variable has a greater influence in measuring purchasing decisions by 35.5%.